PENGARUH MEDIA PEMBELAJARAN BERBASIS POWERPOINT INTERAKTIF TERHADAP MINAT BELAJAR SISWA DALAM PEMBELAJARAN PANCASILA KELAS IV SDN 125 PEKANBARU - Marwan; Nunu Mahnun; Aramudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of interactive PowerPoint-based learning media on students’ learning interest in Pancasila education among fourth-grade students at SDN 125 Pekanbaru. The research employed a quantitative approach with a quasi-experimental design, specifically the Pretest–Posttest Control Group Design. The population consisted of all fourth-grade students of SDN 125 Pekanbaru, with a total sample of 42 students 23 students from class IV-A as the experimental group and 21 students from class IV-B as the control group. The data were collected using a learning interest questionnaire based on a Likert scale, which had been tested for validity and reliability. Data analysis included normality, homogeneity, and independent sample t-tests with a significance level of 0.05. The findings revealed that the average learning interest score of the experimental group increased from 67.30 to 86.52, while the control group’s score rose from 66.95 to 74.43. The calculated t-value of 4.827 with a Sig. (2-tailed) value of 0.000 < 0.05 indicates a significant difference between the two groups. The N-Gain score of 0.59 in the experimental class (moderate to high category) demonstrates a greater improvement in learning interest compared to the control class (N-Gain = 0.22). Based on these results, it can be concluded that the use of interactive PowerPoint-based learning media has a significant positive effect on enhancing students’ learning interest in Pancasila education.